2018
DOI: 10.1093/brain/awy175
|View full text |Cite
|
Sign up to set email alerts
|

Acute ketamine dysregulates task-related gamma-band oscillations in thalamo-cortical circuits in schizophrenia

Abstract: NMDA receptor deficits have been implicated in schizophrenia. Grent-’t-Jong et al. show that treating healthy controls with ketamine triggers changes in neural oscillations during visual processing distinct from those seen in patients with schizophrenia. This suggests that acute NMDA receptor hypofunction does not account for visuo-perceptual deficits in the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 86 publications
4
37
0
Order By: Relevance
“…Secondly, we localized the most consistent differences to the thalamus. While localization of thalamic generators from MEG data remains challenging, we would like to note that reconstruction of MEG time-courses in the thalamus has been consistently demonstrated by our (38,39) and other groups (40). Moreover, our analyses revealed that there were no differences in neighboring structures, such as putamen, pallidum and caudate nucleus, suggesting that signal-leakage, for example, did not contribute to our observations.…”
Section: Strengths and Limitationssupporting
confidence: 69%
“…Secondly, we localized the most consistent differences to the thalamus. While localization of thalamic generators from MEG data remains challenging, we would like to note that reconstruction of MEG time-courses in the thalamus has been consistently demonstrated by our (38,39) and other groups (40). Moreover, our analyses revealed that there were no differences in neighboring structures, such as putamen, pallidum and caudate nucleus, suggesting that signal-leakage, for example, did not contribute to our observations.…”
Section: Strengths and Limitationssupporting
confidence: 69%
“…Our findings clarify how low-dose ketamine triggers its rapid action within the neocortex. Acute sub-anesthetic ketamine administration in healthy volunteers induces schizophrenia-like symptoms and neurocognitive deficits while impacting thalamo-cortical processing distinct from the disease state [53]. At clinically relevant low-dose, we found that cortical response enhancement is borne by 2A subunit-containing NMDA receptors localized to a subset of PV-positive, fast-spiking interneurons.…”
Section: Discussionmentioning
confidence: 98%
“…Results from human studies reveal that an antidepressant dose of ketamine induces an acute enhancement of the power (amplitude) of qEEG oscillations within the 30-to 80-Hz gamma range in the parietal (88), cingulate (88), and cerebral (89) as well as general cortical brain areas (90). Increases in cortical gamma power have been ascribed to a mechanism related to the psychotomimetic actions of ketamine (91)(92)(93), putatively via NMDAR inhibition-mediated modulation of interneuron activity (94). Similar to ketamine, (2R,6R)-HNK administration increases high-frequency cortical gamma qEEG oscillations in mice (15), but unlike ketamine, this metabolite does not exert behavioral changes in the prepulse inhibition task at doses up to 375 mg/kg, indicative of a lack of psychosis potential (15) and relevant NMDAR inhibition (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%